(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article analyzes and discusses the difficulties faced by undergraduate students in academic writing. It highlights the challenges such as plagiarism, lexicology, grammar, lack of understanding that a student can meet during the academic year and tries to give some tips to get rid of these barriers.